OP0279 The Standardised Mortality Rate in UK Adult-Onset Myositis Patients is Seven Times Higher than the UK General Population. (9th June 2015) - Oldroyd, A.G.S.; Newton, L.R.; New, R.P.; Sergeant, J.C.; Cooper, R.G.; Chinoy, H.
Abstract : Background: The idiopathic inflammatory myopathies (IIM) are a group of autoimmune mediated disorders characterised by skeletal muscle inflammation. Identification of factors associated with mortality may allow future interventional measures to reduce mortality. Objectives: To compare mortality rates in a large UK IIM population with those in the general population and to identify clinical, serological and demographic factors associated with mortality. Methods: IIM patients were identified through the UKMYONET study from 84 UK centres. Patients with adult-onset probable or definite polymyositis (PM) or dermatomyositis (DM), or defined inclusion body myositis (IBM) as per accepted criteria (Bohan/Peter, Griggs, MRC) were recruited. Data included demographics, smoking status, cancer diagnosis, clinical features and presence of myositis-specific/associated antibodies (MSA/MAA). Date and cause of death was collated from the UK Health and Social Care Information Service. Age-standardised mortality rates (ASR) per 100, 000 persons were calculated for each gender and IIM subtype. Mortality was compared between IIM subtypes (PM as a reference), clinical features and MSA/MAA subsets using calculated hazard ratios (HRs), adjusted for age, sex and smoking. Results: 724 IIM patients were recruited (62.2% female, 34% smoked, mean age of disease onset 52.4 years [SD 14.9]). Mean symptom onset to diagnosis time was 1.3 years (SD 2.5). 72 (10%) had died at time of analysis. Median time from diagnosis to death for the whole cohort was 12 years (1st quartile 4 years, 3rd quartile 17 years), 8 years for the cancer-associated myositis (CAM) cohort and 16 years for the non-CAM cohort. Mortality risk did not vary between men and women: 10.2% vs 9.8%, p=0.9. 31 deaths were due to pneumonia, 2 interstitial lung disease (ILD), 1 pulmonary embolism, 16 cardiac causes (myocardial infarction, cardiac failure), 11 malignancy, 8 sepsis, 2 IIM and 1 spontaneous haemothorax. Increasing age at onset and smoking history were associated with mortality: HR 1.1 (95% CI 1.1, 1.2) and 2.3 (1.4, 3.8) respectively. Cardiovascular pathology was associated with higher mortality: HR 3.5 (1.2, 10.4). Periorbital oedema was associated with higher mortality in the DM group: HR 6.7 (1.5, 31.5). Table 1 shows that ASRs per 100, 000 persons were more than seven times higher than those in the general UK population: ASR 7559 vs 987/100, 000 persons respectively. IBM ASR was significantly lower than DM and PM for females only. CAM was significantly associated with mortality in men only: HR 5.7 (95% CI 2.5, 13.1). No other IIM subtype, clinical feature (including ILD) or MSA/MAA subsets (including Jo-1) were associated with mortality. Conclusions: This is the first study to investigate factors associated with increased mortality in a large UK IIM population with a verified IIM diagnosis. Mortality rates in IIM are higher than those of the general UK population mainly due to cardiovascular pathology and cancer, with pneumonia being the leading cause of death. Disclosure of Interest: None declared